2005
DOI: 10.1093/nar/gni165
|View full text |Cite
|
Sign up to set email alerts
|

Partial 13C isotopic enrichment of nucleoside monophosphates: useful reporters for NMR structural studies

Abstract: Analysis of the 13C isotopic labeling patterns of nucleoside monophosphates (NMPs) extracted from Escherichia coli grown in a mixture of C-1 and C-2 glucose is presented. By comparing our results to previous observations on amino acids grown in similar media, we have been able to rationalize the labeling pattern based on the well-known biochemistry of nucleotide biosynthesis. Except for a few notable absences of label (C4 in purines and C3′ in ribose) and one highly enriched site (C1′ in ribose), most carbons … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 59 publications
2
7
0
Order By: Relevance
“…We compared and plotted chemical shift difference between NMPs (Jezowska- Trzebiatowska et al 1980;Kishore et al 2005;Eichhorn et al 2012;Kwan 2012) and ID3. The chemical shift difference follows δ (NMP)-δ (ID3) convention, to obtain positive values for differences in δ, because NMPs display mostly downfield shifts relative to those of structured residues.…”
Section: Comparison Of 13 C Chemical Shifts Between Id3 and Nmpsmentioning
confidence: 99%
“…We compared and plotted chemical shift difference between NMPs (Jezowska- Trzebiatowska et al 1980;Kishore et al 2005;Eichhorn et al 2012;Kwan 2012) and ID3. The chemical shift difference follows δ (NMP)-δ (ID3) convention, to obtain positive values for differences in δ, because NMPs display mostly downfield shifts relative to those of structured residues.…”
Section: Comparison Of 13 C Chemical Shifts Between Id3 and Nmpsmentioning
confidence: 99%
“…Here again the ratio of the sum of the intensities of satellite peaks to the sum of the intensities of the satellite and center peaks was used to calculate the absolute enrichment level. Third, for those carbon sites where no quantitative information could be obtained from either the 1D or the 2-bond ( 2 J HN ) HSQC experiments, the absolute enrichment of proton resonances obtained from the 1D 1 H experiments and relative enrichment values obtained from a carbon HSQC spectrum were used to compute the absolute enrichment levels (Walker et al 1982 ; Kishore et al 2005 ).…”
Section: Methodsmentioning
confidence: 99%
“…However, incorporation of site specific isotopically labeled nucleotides into RNA is necessary to overcome the drawbacks of uniform labeling (Johnson et al 2006 ; Johnson and Hoogstraten 2008 ; Schultheisz et al 2008 ; Dayie and Thakur 2010 ; Thakur et al 2010a , b ; Thakur and Dayie 2011 ) as we and others have demonstrated using RNAs labeled with uniform and selective NTPs (Johnson et al 2006 ; Johnson and Hoogstraten 2008 ; Schultheisz et al 2008 ; Dayie and Thakur 2010 ; Thakur et al 2010a , b ; Thakur and Dayie 2011 ). Previous work had focused on site specific labeling using the gluconeogenic carbon sources of glycerol, glycerol and formate, pyruvate, or acetate using either wild type or two mutant E. coli strains (Hoffman and Holland 1995 ; Johnson et al 2006 ; Johnson and Hoogstraten 2008 ; Dayie and Thakur 2010 ; Thakur et al 2010a , b ; Thakur and Dayie 2011 ), and glucose using wild type E. coli (Kishore et al 2005 ). However because E. coli grows readily on glucose with very good yield compared to the other gluconeogenic carbon precursors (Thakur et al 2010a ), it is attractive to explore glucose as an alternative carbon source.…”
Section: Introductionmentioning
confidence: 99%
“…Statistical labeling has also found use in a number of other contexts, including spectral simplification in solid-state NMR (15) and as an aid to residue type identification to facilitate backbone-directed resonance assignment (16). In a preliminary application to nucleic acids, Kishore et al (17) have used a mixture of C-1 and C-2 labeled glucose as a feedstock for E. coli and found some useful labeling patterns in the resulting ribonucleosides, including a high level of enrichment at ribose C1 0 . Since these authors were primarily attempting to achieve nearrandom isotopic distribution, however, details of the isotopomers produced were not reported.…”
Section: Statistical Labeling For Stereospecific Assignmentsmentioning
confidence: 99%